A death of one's own : literature, law, and the right to die - Stark, Jared Louis (Northwestern University Press, 2018)
"To be or not to be--who asks this question today, and how? What does it mean to issue, or respond to, an appeal for the right to die? In A Death of One's Own, the first sustained literary study of the right to die, Jared Stark takes up these timely questions by testing predominant legal understandings of assisted suicide and euthanasia against literary reflections on modern death from the nineteenth and twentieth centuries. Rigorously interdisciplinary and lucidly argued, Stark's wide-ranging discussion sheds critical light on the disquieting bioethical and biopolitical dilemmas raised by contemporary forms of medical technology and legal agency. More than a survey or work of advocacy, A Death of One's Own examines the consequences and limits of the three reasons most often cited for supporting a person's right to die: that it is justified as an expression of personal autonomy or self-ownership; that it constitutes an act of self-authorship, of "choosing a final chapter" in one's life; and that it enables what has come to be called "death with dignity." Probing the intersections of law and literature, Stark interweaves close discussion of major legal, political, and philosophical arguments with revealing readings of literary and testimonial texts by writers including Balzac, Melville, Benjamin, and Améry. A thought-provoking work that will be of interest to those concerned with law and humanities, biomedical ethics, cultural history, and human rights, A Death of One's Own opens new and suggestive paths for thinking about the history of modern death as well as the unsettled future of the right to die" -- From the publisher.